Debt, R&D investment and technological progress: A panel study of Japanese manufacturing firms in the 90s - Kazuo Ogawa (Osaka University, Institute of Social and Economic Research (ISER), 2004)
Based on a panel data set of Japanese manufacturing firms in research-intensive industries, we investigate quantitatively the extent to which debt outstandings in the 90s affected the firm's R&D activities. We find that massive debt outstandings had significantly negative effect on R&D investment in the 90s. We also find that investment on R&D was closely linked to the firm-level total factor productivity growth in the 90s. In fact, ten-percentage-point increase of debt-asset ratio lowered the firm-level total factor productivity growth rate by 0.72 percentage point for 1999-2001 by way of withering R&D activities, while the firm-level TFP growth rate remains almost intact for 1988-91.
Keywords: D21; D24; O32; 330; R&D investment; Debt; Total factor productivity; Schulden; Industrieforschung; Produktivität; Industrie; Schätzung; Japan